SURVEI PEMBINAAN PRESTASI OLAHRAGA KARATE DI TEMBILAHAN KARATE CLUB KABUPATEN INDRAGIRI HILIR - Pasrah Apriani; Aref Vai; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this research is to see how far the karate sport coaching process in Tembilahan Karate Club Indragiri Hilir Regency in achieving achievements. This research was conducted at the Tembilahan Karate Club, Indragiri Hilir Regency. The research was carried out for 6 months from May 2020 to November 2020. In this study the authors took the object of 14 Tembilahan Karate Club athletes, 2 trainers and 2 coaches with a total of 18 people consisting of 13 men and 5 women. This type of research is descriptive research. Based on the results of the research that the author has described in the previous chapter, conclusions can be drawn based on the viewpoint of the coaches and coaches from the data analysis of the performance development of karate in Tembilahan Karate Club, Indragiri Hilir Regency, in the